2013
DOI: 10.1111/wre.12027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within and between sulfonylurea‐resistant and susceptible populations of Schoenoplectus juncoides in Japan

Abstract: To reveal the effects of herbicide selection on genetic diversity in the outcrossing weed species Schoenoplectus juncoides, six sulfonylurea-resistant (SU-R) and eight sulfonylurea-susceptible (SU-S) populations were analysed using 40 polymorphic inter-simple sequence repeat loci. The plants were collected from three widely separated regions: the Tohoku, Kanto and Kyushu districts of Japan. Genetic diversity values (Nei's gene diversity, h) within each SU-S population ranged from h = 0.125 to h = 0.235. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 31 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…The result of the present study is inconsistent with that of ISSR analysis of Japanese S. juncoides populations (Imaizumi et al ., ), in that the latter detected lower levels of genetic diversity in SU‐R populations than in SU‐S populations. The reason of the difference between the results is largely unknown.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The result of the present study is inconsistent with that of ISSR analysis of Japanese S. juncoides populations (Imaizumi et al ., ), in that the latter detected lower levels of genetic diversity in SU‐R populations than in SU‐S populations. The reason of the difference between the results is largely unknown.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, microsatellite analysis revealed a high value of genetic differentiation among populations ( G ST = 0.617 for a total of 21 populations). This value is comparable with those estimated with ISSR data ( G ST = 0.403 for SU‐S populations and G ST = 0.746 for SU‐R populations) (Imaizumi et al ., ). Compared with other weed species, S. juncoides seems to have a higher level of differentiation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations